Nest Construction of a Malayan Vespa tropica (Vespidae, Hymenoptera, Insecta). - Banu, Qamar; Nurul Huda, K. M. (Contributions to Entomology = Beiträge zur Entomologie, 1989)
For the first time, the stepwise construction of the nest of a Vespa tropica leefmansi van der Vecht, was observed. It was built on the ventilator insede a rural house in Selangor, Malaysia. The nest consisted of a single-tier small comb covered by an outer envelope either completely covered or with a narrow opening near the centre. The nest was initiated by a single foundress queen which was joined by two more queens at a later time. The queens shared the works of nestbuilding, larval caring, maintenance of temperature in the nest and nest-guarding activities. Trophallaxis occurred in between adults and larvae. The nest was used by several generations.